Disrupt and restraint: The evolution of cyber conflict and the implications for collective security. Issue 3 (3rd July 2019) - Taillat, Stéphane
ABSTRACT: In the last decade, cyber conflict has become a main feature of international politics and a growing concern for strategic stability and collective security. Unfortunately, cyber conflict suffers from a lack of conceptual clarity about its impact on collective security and a lack of consensus among international actors on how to interpret it. This article proposes to understand cyber conflict as an evolving process driven by two factors: the way in which digital space is configured and the way in which tactical, organizational, strategic, and doctrinal characteristics related to cyber have been included in the field of national and international security. Both tend to encourage offensive behavior but also demonstrate features pointing to restraint.